The faculty lounge : a novel - Mathieu, Jennifer (Dutton, 2024)
"By the acclaimed author of Moxie, a funny, big-hearted adult debut that is at once an ode to teachers, a timely glimpse at today's pressing school-place issues, and a tender character study, following a sprawling cast of teachers, administrators, and staff at a Texas high school"--